Regulatory T Cells, a Viable Target Against Airway Allergic Inflammatory Responses in Asthma - Zhang, Jing; Zou, Yuan; Chen, Longmin; Xu, Qianqian; Wang, Yi; Xie, Min; Liu, Xiansheng; Zhao, Jianping; Wang, Cong-Yi (Frontiers in Immunology, 2022)
Asthma is a multifactorial disorder characterized by the airway chronic inflammation, hyper-responsiveness (AHR), remodeling, and reversible obstruction. Although asthma is known as a heterogeneous group of diseases with various clinical manifestations, recent studies suggest that more than half of the clinical cases are ‘‘T helper type 2 (Th2)-high’’ type, whose pathogenesis is driven by Th2 responses to an inhaled allergen from the environmental exposures. The intensity and duration of inflammatory responses to inhaled allergens largely depend on the balance between effector and regulatory cells, but many questions regarding the mechanisms by which the relative magnitudes of these opposing forces are remained unanswered. Regulatory T cells (Tregs), which comprise diverse subtypes with suppressive function, have long been attracted extensive attention owing to their capability to limit the development and progression of allergic diseases. In this review we seek to update the recent advances that support an essential role for Tregs in the induction of allergen tolerance and attenuation of asthma progression once allergic airway inflammation established. We also discuss the current concepts about Treg induction and Treg-expressed mediators relevant to controlling asthma, and the therapies designed based on these novel insights against asthma in clinical settings.